Malaysian Nurses' Attitudes Toward Suicide and Suicidal Patients: A Multisite Study. Issue 2 (March 2019) - Siau, Ching Sin; Wee, Lei-Hum; Adnan, Tassha Hilda; Yeoh, Seen Heng; Perialathan, Komathi; Wahab, Suzaily
Abstract : The aim of this study was to examine Malaysian nurses' attitudes toward suicide. Nurses from five hospitals participated in this study. Studying the attitudes of nurses toward suicidal patients and its application to nursing professional development practitioners is an important topic. Most nurses were agreeable to assuming responsibility and to be trained in suicide prevention. Suicide-related training should focus on improving the attitudes of nonpsychiatric nurses, those with no experience in caring for suicidal patients, and those with less nursing experience, all of whom reported more negative attitudes toward suicidal patients.